Caesarean-sections in the Press: the said and the not said. - Tatiana Augustinho Rocha; Gilda Maria de Carvalho Abib; Claudia Junqueira Armellini; Jussara Gue Martini; Ana Lúcia de Lourenzi Bonilha (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
This paper aimed at knowing the cultural caesarean representations present in magazines addressed to the laic public. One of the attributions of the nurse is health education. The press is source of informal education. So, the nurse must provide women with subsidies so that they can make decisions with autonomy and knowledge, demystifying or incrementing what is thought about the surgical delivery. Upon analyzing editions of Revista Crescer, two themes have arisen: the "said" and the "not said" about caesarean. Regarding the "said" category, the articles appraise pathologies in the gestation and their inter-occurrences with explicit association between pathologies and the caesarean; the magazine searched for the adequacy of the woman to the hospital routine and softened the caesarean consequences. As to the "not said" category, the magazine did not emphasize the control and prevention of the complications that are inherent to pregnancy and, somehow, led women to opt for the caesarean as the safest mode of delivery.